Bisphosphonate-induced Osteonecrosis of the Jaws: Review, Clinical Implications and Case Report - Suleman, Yusuf Farouk (Humana Press Inc, 2007)
The introduction of bisphosphonates has increased in the last decade following their indication for metastatic bone diseases, osteoporosis, hypercalcaemia of malignancy and Paget’s disease. Although bisphosphonates have been used clinically for more than three decades there have been no documented long-term complications of their effects on the jaws until recently, where there is now growing evidence of the influence of bisphosphonates on osteonecrosis of the jaws. The aim of this paper is to report a case of this newly described complication, to review this phenomenon, including the clinical implications and to reiterate current clinical guidelines for management of patients in which bisphosphonate therapy is indicated. To the best of our knowledge this is the first reported case of bisphosphonate-induced necrosis of the jaw in South Africa.